2015
DOI: 10.1590/1516-1439.000814
|View full text |Cite
|
Sign up to set email alerts
|

Stibnite Nanoparticles as a New Stabilizer for Poly (Methyl Methacrylate) Exposed to Gamma Irradiation

Abstract: Poly (methyl methacrylate), PMMA, may be used in manufacturing of devices, which are exposed to gamma irradiation. However, the polymer undergoes significant changes in its properties during process and the use of additives is a common form to stabilize the PMMA matrix. In this way, stibnite was synthesized by sonochemical method and the amorphous powder constituted of nanospheres was obtained and investigated as additive. Commercial PMMA containing stibnite nanoparticles (ST-NP) was investigated and the sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Stabilizers like free radical scavengers (primary antioxidants) can prevent the main scission and cross-linking 13,21 . In addition, our most recent studies have shown the efficiency of using nanoparticles in the same amount of commercial additives as stabilizers for PMMA and Poly (vinyl chloride) (PVC) exposed to gamma radiation [22][23][24][25] .…”
Section: Commercial Additives For Polymer Matrixmentioning
confidence: 99%
“…Stabilizers like free radical scavengers (primary antioxidants) can prevent the main scission and cross-linking 13,21 . In addition, our most recent studies have shown the efficiency of using nanoparticles in the same amount of commercial additives as stabilizers for PMMA and Poly (vinyl chloride) (PVC) exposed to gamma radiation [22][23][24][25] .…”
Section: Commercial Additives For Polymer Matrixmentioning
confidence: 99%
“…In addition, a decrease in ZnS stabilizing action occurred when its concentration reached 1.00 %wt. This is a rather common effect in polymer-additives systems as optimum additive concentration is overreached 13,14 .…”
Section: Radiostabilizing Action Of Zns Nanocrystals In Pvc Matrixmentioning
confidence: 99%
“…These extreme transient conditions allow synthesis on the benchtop, at room-temperature conditions, in media that would otherwise require high temperatures, high pressures, or long reaction times 11,12 . Zinc sulfide sonochemical synthesis is a suitable preparation method, which allows fast and simple obtention of morphologically pure products [13][14][15][16][17][18] , circumventing tedious and laborious methods already described in the literature 19,20 . PVC has applications that range from rigid pipes to electron-beam or gamma irradiation sterilizable medical devices..…”
mentioning
confidence: 99%